Asesoramiento psicopedagógico en el proceso de lectoescritura por estudiantes de educación general básica superior - Mendoza-Mera, Jean Telmo; Arroyo-Carrera, Eugenia Narcisa; Loor-Santos, María Valentina; Solorzano-Zambrano, Mónica Elizabeth (Revista Arbitrada Interdisciplinaria Koinonía, 2020)
The objective of the research was to analyze the importance of psychopedagogical counseling in the literacy process by students of higher general basic education in Ecuador, through a documentary review with bibliographic design of research works related to psychopedagogy and learning problems through literacy, located in peer-reviewed journals and indexed in databases recognized for good editorial practice. Six central indicators are configured to promote psycho-pedagogical strategies in order to promote an effective process of literacy in students of general basic education, which generates a multidisciplinary articulation, therefore, neuroscience must be addressed as a promoter approach to an education where they are addressed neural and affective networks in order to stimulate cognition, through the effective use of ICT in order to promote research and reflection as a fundamental axis of learning.